Eye reflux: an ocular extraesophageal manifestation of gastric reflux - Mazzacane, Danilo (Int J Ophthalmol, 2018)
AIM: To suspect laryngopharyngeal reflux (LPR) in patients with ocular surface disease (OSD). METHODS: The present study evaluated a group of subjects with OSD assessing the Ocular Surface Disease Index (OSDI) and the Reflux Symptom Index (RSI) to detect patients with suspected LPR and define a possible relationship between tests. RESULTS: Two hundred and ninety subjects (175 females, mean age: 60.41±15.68y) were consecutively visited at ophthalmologist offices. One hundred and one (34%) patients had pathological RSI (>13) and consequently a suspected LPR. CONCLUSION: The current study shows that suspected LPR may be common (34%) in patients with OSD and a suspected LPR may be considered in OSD patients when RSI score is >13 and OSDI score is >42.